The fundamentals of eeg signal processing - Kamel, N. (CRC Press, 2014)
It is common knowledge that a signal contains information about the behavior or nature of some phenomenon. The task of biomedical signal processing in general is to extract useful information contained in the signal. The method used to extract this information depends on the nature of the signal and the kind of information contained in it. In fact, there is no unique way to process signals for information extraction but rather a wide range of approaches. Generally speaking, the first step in extracting information from the signals is selecting the right analytical representation. This representation can be achieved through basis functions in the original domain of occurrence or in a transformed domain. Similarly, the process of information extraction may be performed in either domain. Â© 2015 by Taylor & Francis Group, LLC.